Generation of Anisotropic Au Nanostructures in Aqueous Carboxymethyl Cellulose Matrix for Potential Catalytic Application. Issue 48 (30th December 2019) - Borgohain, Xavy; Yomcha, Jarpum; Khan, Aslam; Rashid, Md. Harunar
Abstract: Carboxymethyl cellulose; Na‐salt (Na‐CMC), an economical and safe carbohydrate molecule has been successfully used as a reducing‐cum‐shape‐directing agent to prepare anisotropic Au nanostructures at room temperature. To better understand the growth habits, Au nanostructures have also been prepared using Na‐CMC at a higher temperature. Electron microscopy analysis confirmed the formation of tape‐like Au nanostructures at room temperature which are composed of triangular‐shaped structures attached orientally along (111) direction. Visual observation indicated a higher rate of formation of Au nanostructures at higher temperatures and hence thermodynamically stable nearly spherical Au nanoparticles are formed. Kinetic studies revealed that at room temperature, the formation of tape‐like structures starts from the beginning due to the assembled structures of Na‐CMC in water. These tape‐like Au nanostructures exhibit excellent catalytic performance in the borohydride reduction of p ‐nitrophenol with maximum apparent rate constant, k app value of 2.3 × 10 ‐2 s ‐1 . Abstract : A simple but effective green method is reported to synthesize anisotropic Au nanostructures in carboxymethyl cellulose matrix at room temperature for catalytic reduction of p ‐nitrophenol in an aqueous medium.